2021
DOI: 10.3390/coatings11080923
|View full text |Cite
|
Sign up to set email alerts
|

Physical Properties of Fe3Si Films Coated through Facing Targets Sputtering after Microwave Plasma Treatment

Abstract: Fe3Si films are deposited onto the Si(111) wafer using sputtering with parallel facing targets. Surface modification of the deposited Fe3Si film is conducted by using a microwave plasma treatment under an Ar atmosphere at different powers of 50, 100 and, 150 W. After the Ar plasma treatment, the crystallinity of the coated Fe3Si films is enhanced, in which the orientation peaks, including (220), (222), (400), and (422) of the Fe3Si are sharpened. The extinction rule suggests that the B2–Fe3Si crystallites are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…1 a reveals a dominant Fe 3 Si(222) peak at 56.34° with Si(111) at 28.46°. This result correlates with our previous works, where we reported that Fe 3 Si deposited at low temperatures through FTS caused a superposition peak in the B2 structure [ 1 , 2 ]. After RTA at 200 °C–400 °C, the Fe 3 Si(222) and Si(111) peak intensifies as the T RTA value increases.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…1 a reveals a dominant Fe 3 Si(222) peak at 56.34° with Si(111) at 28.46°. This result correlates with our previous works, where we reported that Fe 3 Si deposited at low temperatures through FTS caused a superposition peak in the B2 structure [ 1 , 2 ]. After RTA at 200 °C–400 °C, the Fe 3 Si(222) and Si(111) peak intensifies as the T RTA value increases.…”
Section: Resultssupporting
confidence: 92%
“…Ferromagnetic silicide (Fe 3 Si), comprising crystals with a diameter range of less than 10 nm, is a recent innovation and a fascinating spin transistor material and possible candidate for self-cleaning surfaces and hard coating applications [ [1] , [2] , [3] ]. This kind of composite can be formulated from environmentally friendly elements that are abundant on the earth like Si and Fe.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ferromagnetic silicide (Fe 3 Si), composed of naturally available materials (Si and Fe), is known to be appealing in the plausible application of spin transistors and self-cleaning surfaces [1][2][3][4]. Prior related studies show that the epitaxial production of Fe 3 Si films onto 111-oriented Si wafers can be achieved via the usage of facing target sputtering (FTS) [5,6].…”
Section: Introductionmentioning
confidence: 99%